Respostas
respondido por:
3
x⁴ + 4x² + 4 = 2x² + 12
x⁴ + 2x² - 8 =0
(x²)² + 2x² -8 = 0
y² + 2y - 8 =0
Δ = 36
y₁ = 4/2
y₁ =2
y₂ = -6/2
y₂ = -3
para y = 2 temos
x² = 2
x = +√2 , -√2
x² = -3 ⇒ x = + √ -3 , - √-3 nao pertence IR
logo, S = { -√2, +√2}
x⁴ + 2x² - 8 =0
(x²)² + 2x² -8 = 0
y² + 2y - 8 =0
Δ = 36
y₁ = 4/2
y₁ =2
y₂ = -6/2
y₂ = -3
para y = 2 temos
x² = 2
x = +√2 , -√2
x² = -3 ⇒ x = + √ -3 , - √-3 nao pertence IR
logo, S = { -√2, +√2}
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás